2021
DOI: 10.1111/jomf.12787
|View full text |Cite
|
Sign up to set email alerts
|

Support exchanges between adult children and their parents across life transitions

Abstract: Objective This study examined whether adult children's transitions to marriage, parenthood, and divorce were related to intergenerational support exchanges. Background Intergenerational support fluctuates over the life span, often in response to major transitions, but surprisingly little research has examined longitudinally how life transitions shape the bidirectional flow of intergenerational support. Method Using data from adult children who participated in Waves 2, 4, 6, and 8 of the German Family Panel (pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…These delays result from rising costs of independent living, stagnation of wages, and decreasing employment opportunities for young adults (Fry, 2017; J. Lee et al, 2020; Min et al, 2022). Consequently, today’s emerging adults have become more economically and socially dependent on their parents than in past generations (Fingerman, 2017).…”
Section: Intergenerational Solidaritymentioning
confidence: 99%
See 2 more Smart Citations
“…These delays result from rising costs of independent living, stagnation of wages, and decreasing employment opportunities for young adults (Fry, 2017; J. Lee et al, 2020; Min et al, 2022). Consequently, today’s emerging adults have become more economically and socially dependent on their parents than in past generations (Fingerman, 2017).…”
Section: Intergenerational Solidaritymentioning
confidence: 99%
“…Changes in relationships following life transitions have been observed. For instance, after marrying or partnering, adult children tend to receive less emotional support from their parents, particularly from their mothers, and also provide less emotional support to their parents (Min et al, 2022). When adult children become parents themselves, they are less likely to provide emotional and instrumental support to their parents (Min et al, 2022).…”
Section: Intergenerational Solidaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Older respondents have to look back further in time when answering questions about their childhood, which could result in biased reports as experiences that occurred later in life might influence the evaluation of the past (de Vries & de Graaf, 2008 ; Karney & Coombs, 2000 ). Finally, we include some characteristics of the greater family network, which, in line with the linked live perspective, have been shown to affect the parent–child relationship, such as the anchor’s life course stages of being partnered and having children (Kalmijn, 2007 , 2015b ; Min et al, 2022 ; Ward et al, 2014 ), and whether the mother had a new cohabiting relationship (King, 2006 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We consider the effects of parents' SES in combination with the role of children's life courses. Several studies in the past have shown that parental support for children changes across the life course (Brandt et al, 2008; Bucx et al, 2012; Kalmijn, 2019; Min et al, 2022; Nazio & Saraceno, 2013; Silverstein et al, 2002). Support tends to decline as children age, but on top of aging effects, there are significant effects of marriage, parenthood, and divorce.…”
mentioning
confidence: 99%